Identifying the critical success practices of sustainability and their implementation in the manufacturing sector of Pakistan: an exploratory factor analysis - Asif Nawaz Wassan; Muhammad Saad Memon; Sonia Irshad Mari; Muhammad Ahmed Kalwar (Journal of Applied Research in Technology & Engineering, 2023)
The concept of sustainability is increasingly discussed in organizations whether they are large firms or SMEs as a sign of environmental awareness of consumer knowledge of product quality. This study provides a better understanding of how sustainability practices are being implemented in the manufacturing sector which is one of the most promising sectors in the world. The aim of this paper is to identify the critical success factors of sustainability and their implementation in the manufacturing industries. The data was collected through a questionnaire survey from the manufacturing industries of Karachi and Hyderabad Sindh Pakistan. In-depth information about the sustainability concept in the company was collected by using the questionnaire survey technique. The data was analysed by using descriptive and exploratory factor analysis. The study also developed a conceptual framework that helps in improving the business, sustainability, and financial performance. This framework consists of three practices (economic, environmental and social) with twelve sub-practices (Cost management, research and development, limited landfilling, Environmental pollution, product lifecycle, resource consumption, public welfare, industrial health and safety, and stakeholder) of sustainability, these practices aim is to bring effective performance in the manufacturing industries of Pakistan. The proposed framework of this study will give an important vision that will enable Pakistani industries to get benefit from the sustainability implementation. Moreover, this study will also provide an understanding of how sustainability would help manufacturing industries to obtain a competitive advantage in the global marketplace. The finding of this study would serve as a guideline for business management as they developed a strategy for achieving sustainable performance. Additionally, this study will offer a preliminary step for future research on manufacturing industries in sustainable manufacturing.